A rapid national survey of terrestrial and semi-aquatic mammals using environmental DNA metabarcoding - Holly A. Broadhurst; Elin E. Smith; Jake M. Jackman; Robert Raynor; Claire Howe; Naiara Guimarães Sales; Allan D. McDevitt (Mammalian Biology, 2026)
Assessing the distribution and diversity of terrestrial and semi-aquatic mammals is fundamental for effective conservation efforts. Environmental DNA (eDNA) metabarcoding has emerged as a rapid and cost-effective method for surveying mammals. It has promising avenues for conducting national surveys and enabling comprehensive assessments of mammalian populations across diverse habitats. We collected eDNA samples from 60 water systems across six regions in England (from north to south), United Kingdom, over a period of up to four days in each region. We detected 26 mammals from five taxonomic orders across all sampling locations, recovering 53–89% of the known mammal community in each region. Our findings underscore the feasibility of utilising eDNA metabarcoding for rapidly surveying mammal populations on a national scale, potentially complementing data from existing surveys/records or implementing in data deficient regions. However, challenges remain for surveying certain species using this method, with varying levels of detectability of key species (e.g. otters) across regions.

Brain volume in chronic ketamine users — relationship to sub-threshold psychotic symptoms and relevance to schizophrenia - Robert A. Chesters; Fiona Pepper; Celia Morgan; Jonathan D. Cooper; Oliver D. Howes; Anthony C. Vernon; James M. Stone (Psychopharmacology, 2022)
Rationale Ketamine may model aspects of schizophrenia arising through NMDA receptor activity deficits. Although acute ketamine can induce effects resembling both positive and negative psychotic symptoms, chronic use may be a closer model of idiopathic psychosis. Objectives We tested the hypotheses that ketamine users had lower brain volumes, as measured using MRI, and greater sub-threshold psychotic symptoms relative to a poly-drug user control group. Methods Ketamine users (n = 17) and poly-drug using controls (n = 19) were included in the study. All underwent volumetric MRI imaging and measurement of sub-threshold psychotic symptoms using the Comprehensive Assessment of At-Risk Mental State (CAARMS). Freesurfer was used to analyse differences in regional brain volume, cortical surface area and thickness between ketamine users and controls. The relationship between CAARMS ratings and brain volume was also investigated in ketamine users. Results Ketamine users were found to have significantly lower grey matter volumes of the nucleus accumbens, caudate nucleus, cerebellum and total cortex (FDR p < 0.05; Cohen’s d = 0.36–0.75). Within the cortex, ketamine users had significantly lower grey matter volumes within the frontal, temporal and parietal cortices (Cohen’s d 0.7–1.31; FDR p < 0.05). They also had significantly higher sub-threshold psychotic symptoms (p < 0.05). Frequency of ketamine use showed an inverse correlation with cerebellar volume (p < 0.001), but there was no relationship between regional brain volumes and sub-threshold psychotic symptoms. Conclusions Chronic ketamine use may cause lower grey matter volumes as well as inducing sub-threshold psychotic symptoms, although these likely arise through distinct mechanisms.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A dual compartment cuvette system for correcting scattering in whole-cell absorbance spectroscopy of photosynthetic microorganisms - John R. D. Hervey; Paolo Bombelli; David J. Lea-Smith; Alan K. Hulme; Nathan R. Hulme; Atvinder K. Rullay; Robert Keighley; Christopher J. Howe (Photosynthesis Research, 2022)
Absorption spectroscopy is widely used to determine absorption and transmission spectra of chromophores in solution, in addition to suspensions of particles, including micro-organisms. Light scattering, caused by photons deflected from part or all of the cells or other particles in suspension, results in distortions to the absorption spectra, lost information and poor resolution. A spectrophotometer with an integrating sphere may be used to alleviate this problem. However, these instruments are not universally available in biology laboratories, for reasons such as cost. Here, we describe a novel, rapid, and inexpensive technique that minimises the effect of light scattering when performing whole-cell spectroscopy. This method involves using a custom made dual compartment cuvette containing titanium dioxide in one chamber as a scattering agent. Measurements were conducted of a range of different photosynthetic micro-organisms of varying cell size and morphology, including cyanobacteria, eukaryotic microalgae and a purple non-sulphur bacterium. A concentration of 1 mg ml −1 titanium dioxide, using a spectrophotometer with a slit width of 5 nm, produced spectra for cyanobacteria and microalgae similar (1–4% difference) to those obtained using an integrating sphere. The spectrum > 520 nm was similar to that with an integrating sphere with the purple non-sulphur bacterium. This system produced superior results to those obtained using a recently reported method, the application of the diffusing agent, Scotch™ Magic tape, to the side of the cuvette. The protocol can be completed in an equivalent period of time to standard whole-cell absorbance spectroscopy techniques, and is, in principle, suitable for any dual-beam spectrophotometer.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Publisher Correction to: Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Leveraging a Landscape-Level Monitoring and Assessment Program for Developing Resilient Shorelines throughout the Laurentian Great Lakes - Donald G. Uzarski; Douglas A. Wilcox; Valerie J. Brady; Matthew J. Cooper; Dennis A. Albert; Jan J. H. Ciborowski; Nicholas P. Danz; Anne Garwood; Joseph P. Gathman; Thomas M. Gehring; Greg P. Grabas; Robert W. Howe; et al. (Wetlands, 2019)

The effects of cannabinoid 1 receptor compounds on memory: a meta-analysis and systematic review across species - Faith Borgan; Katherine Beck; Emma Butler; Robert McCutcheon; Mattia Veronese; Anthony Vernon; Oliver D. Howes (Psychopharmacology, 2019)

Altered glutamatergic response and functional connectivity in treatment resistant schizophrenia: the effect of riluzole and therapeutic implications - Toby Pillinger; Maria Rogdaki; Robert A. McCutcheon; Pamela Hathway; Alice Egerton; Oliver D. Howes (Psychopharmacology, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Mass-Spring Model for Simulation of Heart Valve Tissue Mechanical Behavior - Peter E. Hammer; Michael S. Sacks; Pedro J. del Nido; Robert D. Howe (Annals of Biomedical Engineering, 2011)

Surface texture can bias tactile form perception - Masashi Nakatani; Robert D. Howe; Susumu Tachi (Experimental Brain Research, 2011)

Cigarette smoking, body mass index, gastro-esophageal reflux disease, and non-steroidal anti-inflammatory drug use and risk of subtypes of esophageal and gastric cancers by P53 overexpression - Jonine D. Figueroa; Mary Beth Terry; Marilie D. Gammon; Thomas L. Vaughan; Harvey A. Risch; Fang-Fang Zhang; David E. Kleiner; William P. Bennett; Christine L. Howe; Robert Dubrow; Susan T. Mayne; Joseph F. Fraumeni; et al. (Cancer Causes & Control, 2009)